Cobitis keyvani, a junior synonym of Cobitis faridpaki (Teleostei: Cobitidae) - Jouladeh-Roudbar, Arash; Eagderi, Soheil; Sayyadzadeh, Golnaz; Esmaeili, Hamid Reza (Zootaxa, 2017)
The validity of C. keyvani and C. faridpaki is assessed based on morphological and molecular (COI) data from fishes collected from the type localities of both species. No diagnostic character was found to distinguish both species. Therefore, we treat C. keyvani as a junior synonym of C. faridpaki.